Boosting photocurrent of GaInP top-cell for current-matched III–V monolithic multiple-junction solar cells via plasmonic decahedral-shaped Au nanoparticles. (15th May 2018) - Bai, Yiming; Yan, Lingling; Wang, Fuzhi; Yang, Yun; Liu, Huiyun; Yin, Zhigang; Chen, Nuofu; Hayat, Tasawar; Alsaedi, Ahmed; Tan, Zhan'ao
Highlights: Au decahedral nanoparticles are obtained using the AgNO3 -assisted chemical method. Au decahedra desires better optical properties than that of sphere and ellipsoid. Au nanoparticles are successfully applied to boost absorption of GaInP top-cell. Multiple-junction solar cells with Au nanoparticles demonstrate higher efficiency. The plasmonic Au light trapping structure also highlights non-annealing treatment. Abstract: Unbalanced photocurrent output for each sub-cell in monolithic multiple junction solar cells (MMJ-SCs) reduces the achievable photovoltaic power efficiency (PCE). Here, we first introduce Au decahedra nanoparticles to realize the plasmon-enhanced photo-absorption of GaInP top-cell and achieve the current-matched MMJ-SCs. By simply spin-coating the Au decahedral nanoparticles on the illuminated surface of the devices, the PCEs of the monolithic double junction and triple junction solar cells increase significantly from 27.01% to 28.63% and from 29.88% to 31.90%, respectively. Both the theoretical local electromagnetic distributions and the experimental extinction properties confirm the plasmonic induced absorption enhancement in device performance, and further elucidate the essential reason for photocurrent enhancement derives from the more furious oscillation of free electrons in the vicinity of sharp vertexes for Au decahedra nanoparticles. Our results demonstrate that Au decahedra with sharp vertexes and edges are promising for meliorating the trade-off between light absorption and carrier collection in GaInP top-cell. In addition, this facile and simple strategy also highlights non-annealing treatment and prevents the impurity diffusion at high temperature for MMJ-SCs, and may facilitate other types of solar-harvesting devices.